The linkage of innate and adaptive immune response during granulomatous development - Ito, Toshihiro; Connett, Judith M.; Kunkel, Steven L.; Matsukawa, Akihiro (Frontiers in Immunology, 2013)
Granulomas represent a spectrum of inflammatory sequestration responses that may be initiated by a variety of agents, including noninfectious environmental factors and infectious microbial pathogens. Although this reaction is designed to be protective, the associated tissue injury is often responsible for a profound degree of pathology. While many of the mechanisms that sustain the development of the granuloma are enigmatic, it is accepted that the maintenance of this inflammatory process is dependent upon dynamic interactions between an inciting agent, inflammatory mediators, various immune and inflammatory cells, and structural cells of the involved tissue. The best studied of the host-dependent processes during granuloma development is the innate and adaptive immune response. The innate immune response by antigen-presenting cells (APCs; Dendritic cells and macrophages) is initiated quickly to protect from overwhelming pathogens, but with time, can also activate the adaptive immune response. APCs, essential regulators of the innate immune response, can respond to microbial ligands through Toll-like receptors (TLRs), which function in the recognition of microbial components and play an important role to link the innate and adaptive immune responses. CD4+ T helper cells are essential regulators of adaptive immune responses and inflammatory diseases. Recently, the Notch system has been shown to be an important bridge between APCs and T cell communication circuits. In the present review, we discuss recent findings that explore the mechanisms in the linkage of innate and adaptive immunity, including granulomatous formation though TLRs and Notch activation.